Labour productivity convergence and structural changes: Simultaneous analysis at country, regional and industry levels - Amjad Naveed; Nisar Ahmad (Journal of Economic Structures, 2016)
Many structural changes have occurred in the European Union countries, for example, there have been changes in sectoral employment share, in the demand of goods due to technology, in trade patterns and in technology. These structural changes may affect the process of convergence. Most of the existing studies on convergence have ignored the role of structural change, which may have resulted in different conclusion. This study considers the role of structural change in testing labour productivity convergence and its speed at the country, region and industry levels simultaneously. The results show that conditional convergence exists at country, regional and industry levels. However, speed of convergence is different across different aggregation levels. Convergence speed at the regional levels is faster than at the country and industry levels. Furthermore, if we do not incorporate structural change, convergence speed may be over- or underestimated.
Keywords: C31; D24; O49; O52; R10; 330; Labour productivity; Convergence; Structural changes; Country; Regional and industry